Nanotechnology in interventional cardiology: A state-of-the-art review. (December 2022) - Almas, Talal; Haider, Rakhshan; Malik, Jahanzeb; Mehmood, Asim; Alvi, Areej; Naz, Hifza; Satti, Danish Iltaf; Zaidi, Syed Muhammad Jawad; AlSubai, Abdulla K.; AlNajdi, Sara; Alsufyani, Reema; Ramtohul, Rahul Krylov; et al.
Abstract: Despite the contemporary techniques and devices available for invasive cardiology procedures, the current diagnostic, and interventional modalities have many shortcomings. As a contemporary cross-disciplinary technique, nanotechnology has demonstrated great potential in interventional cardiology practice. It has a pivotal role in detecting sensitive cardiac biomarkers, nanoparticle-enhanced gadolinium (Gd) contrast to enhance the detection of atherosclerotic cardiovascular disease (ASCVD), and multimodal imaging like including optical coherence tomography (OCT)/infrared luminescence (IR) for coronary plaque characterization. Furthermore, in invasive cardiology, the potential benefit is in miniaturized cardiac implantable electronic devices (CIEDs), including leadless pacemakers and piezoelectric nanogenerators to self-power symbiotic cardiac devices. Nanoparticles are ideal for therapeutic drug delivery systems for atherosclerotic plaque regression, regeneration of fibrotic cardiomyocytes, and disruption of bacterial biofilm to enhance and prolong the effects of antimicrobial agents in infective endocarditis (IE). In summary, nanotechnology-assisted therapies can overtake conventional invasive cardiology and expand the horizon of microtechnology in the diagnosis and treatment of CAD in the foreseeable future.